Assigning regioisomeric or diastereoisomeric relations of problematic trisubstituted double-bonds through heteronuclear 2D selective J-resolved NMR spectroscopy1. Issue 47 (27th May 2015) - Hoffmann, Marie; Miaskiewicz, Solène; Weibel, Jean-Marc; Pale, Patrick; Blanc, Aurélien
<x xml:space="preserve">Abstract</x> Although one of the first 2D NMR methods, but so far neglected, selective J-resolved NMR spectroscopy offers a unique opportunity to help organic chemists in structure elucidation, avoiding natural and non-natural product misassignments.